New prospects for assessing the hemostasis system in atrial fibrillation and left atrial appendage thrombosis - Z. A. Gebekova; I. I. Ivanov; A. A. Kudrjavtseva; E. V. Kolpachkova; A. A. Sokolova; V. P. Sedov; D. A. Napalkov («REMEDIUM GROUP» Ltd., 2023)
Thromboembolic syndrome, the frequency of which is 8-15%, is the main danger for a patient with atrial fibrillation (AF). The left atrial appendage is the most common source of thromboembolia in atrial fibrillation. The frequency of detection of left atrial appendage thrombus in AF is 15.2% in the absence of anticoagulant therapy and 1-8% in patients using this group of drugs. The reason for the formation of thrombi in this localization during anticoagulant therapy today it is not reliably known. This article describes a clinical case of a 67-year-old patient with persistent AF and left atrial appendage thrombosis, who was hospitalized to determine further management strategies. A left atrial appendage thrombus lasted for a year despite continuous anticoagulant therapy with various oral anticoagulants at doses consistent with clinical guidelines due to the patient's absolute refusal to take warfarin, vitamin K antagonist. In addition, this article discusses the use of Thrombodynamics, a new global coagulation test, in patients with AF, which revealed a plasma hypercoagulable state with underlying persistent thrombosis in this patient on continuous oral anticoagulant treatment. The Thrombodynamics test is a promising procedure for assessing the coagulation system state and may be promising as a method for measuring the effectiveness of any oral anticoagulant. However, it is impossible to draw any definite conclusions on the basis of single observations; large clinical studies with the potential of long-term case follow-up of patients are needed.